Analisis dan Model Dispersi Emisi Udara di TPA Klotok, Kediri: Dispersion Analysis and Model of Air Emissionin Klotok Landfill, Kediri - Jawwad, Muhammad Abdus Salam; Murti, Restu Hikmah Ayu; Citrasari, Nita (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2023)
Klotok landfill is a final waste processing site in the City of Kediri that has been operating since 1992 to manage waste in the Kediri City and its surroundings. Waste management activities at the Klotok TPA generate emissions from the waste pile and heavy equipment activities. This study aims to determine the air quality at the Klotok Landfill through direct measurements to obtain results with a more accurate approach. The measurement results will then be modeled with AERMOD software to determine the distribution of these pollutants to the area around the TPA. In this study, air quality measurements were carried out at three points in the Klotok TPA to determine the level of pollution that occurred. Air quality is measured directly using a High Volume Air Sampler (HVAS), Impinger, and Sound Level Meter. Air pollutant parameters measured included Nitrogen Dioxide (NO2), Total Suspended Particulate (TSP), Sulfur Dioxide (SO2), Oxidants (O3), Carbon Monoxide (CO), Lead (Pb), Non-Methane Hydrocarbons (NMHC), Particulate Matter 2.5 (PM2.5), PM10, Ammonia (NH3), and noise. The measurement results show that the CO parameter exceeds theambient air quality standards of PP No. 22 Year 2021 at the weighbridge and the landfill 3 with values of 13,750 and 18,750 µg/Nm3 respectively,while other parameters still meet the quality standard. The model with AERMOD software shows the dispersion of CO nearby the landfill area occurs quickly so that since the first 100 meters the CO concentration has been dispersed to below 10 µg/Nm3. CO concentrations at a distance of more than 1 km from the Klotok TPA are generally below 1 µg/Nm3.